An Evaluation of Glucagon Injection Anxiety and Its Association with the Fear of Hypoglycemia among the Parents of Children with Type 1 Diabetes - Serra Muradoğlu; Gül Yeşiltepe Mutlu; Tuğba Gökçe; Ecem Can; Şükrü Hatun (Galenos Yayincilik, 2021)
Objective:Hypoglycemia is a common acute complication of type 1 diabetes (T1D), which may cause seizure, loss of consciousness, and temporary motor or sensory impairment. Glucagon administration is an effective way of treating severe hypoglycemia, especially in a free-living setting. Nonetheless, families have difficulties in managing severe hypoglycemia due to their anxiety and challenges with current glucagon administration techniques. The aim of the current study was to explore the associations between parental fear of hypoglycemia (FoH) and their general anxiety level, and in particular, their attitudes towards and thoughts on glucagon administration.Methods:Parents of children with T1D completed questionnaires assessing background and clinical information, FoH, generalized anxiety disorder (GAD) and parental anxiety for glucagon administration (PAGA).Results:Sixty-eight parents participated. Positive correlations were found between parental GAD-7 score and both FoH and the number of night-time blood glucose measurements and there was a negative correlation with the child's age. Parents mean self-evaluation score of their competence in glucagon administration was 6 (standard deviation±2.9) on a scale of 0 to 10. Unsurprisingly, this score was negatively correlated with the PAGA scores. There was no significant difference between children using continuous glucose monitoring system and self-monitoring of blood glucose in terms of parental FoH, anxiety and misconceptions about glucagon administration.Conclusion:The results showed that parents of children with T1D had anxiety and fear connected with hypoglycemia and glucagon administration. Structured and practical training should be implemented to increase parents' self-confidence including annual refresher training for home glucagon administration.